Mentoring: creating meaning by sharing knowledge, values, and skills - Heiser, Deborah (Henry Stewart Talks, 2025)
Mentoring, The Mentor Project, Generativity, Intrinsic motivation, Alignment of values, AI, Lateral mentoring